Analisis Ancaman Terhadap Penerapan Framework Manajemen Insiden Di Indonesia - Kurniawan, Rizky Hendra; Ras, Abdul Rivai (Jurnal Kajian Stratejik Ketahanan Nasional, 2019)
The incident management framework is a tools that can be used as an early warning system to overcome problems in the implementation of information technology. This Framework also used for measuring the maturity level of incident management that has been carried out by institutions in Indonesia. We can used it as an open intelligence of information source. Within national scope, this framework used for knowing Indonesia’s ability to deal with cyber incidents. Therefore, it is necessary to conduct a threat analysis on the implementation of incident management framework. Author used mix-methode research, which is the combination between qualitative and quantitative research. The result of this research is coefficient value of threat analysis to the implementation of incident management is 15.86. This value is included in high category.